2008
DOI: 10.1158/0008-5472.can-08-0796
|View full text |Cite
|
Sign up to set email alerts
|

AlkB Homologue 2–Mediated Repair of Ethenoadenine Lesions in Mammalian DNA

Abstract: Endogenous formation of the mutagenic DNA adduct 1,N 6 -ethenoadenine (EA) originates from lipid peroxidation. Elevated levels of EA in cancer-prone tissues suggest a role for this adduct in the development of some cancers. The base excision repair pathway has been considered the principal repair system for EA lesions until recently, when it was shown that the Escherichia coli AlkB dioxygenase could directly reverse the damage. We report here kinetic analysis of the recombinant human AlkB homologue 2 (hABH2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 42 publications
6
75
0
Order By: Relevance
“…Recently, another direct reversal pathway mediated by ABH2 dioxygenase has been identified in mammalian cells (Ringvoll et al 2008). This protein can directly repair 1,N 6 -ethenoadenine adducts in nDNA in an iron, oxoglutarate-dependent manner.…”
Section: Direct Reversalmentioning
confidence: 99%
“…Recently, another direct reversal pathway mediated by ABH2 dioxygenase has been identified in mammalian cells (Ringvoll et al 2008). This protein can directly repair 1,N 6 -ethenoadenine adducts in nDNA in an iron, oxoglutarate-dependent manner.…”
Section: Direct Reversalmentioning
confidence: 99%
“…Finally the apex1 gene which is a component of the base excision repair mechanism, 48 xrcc5 which repairs double strand breaks in zebrafish embryos, 49 and the alkbh2 gene which is involved in repairing DNA etheno adducts, 50 were upregulated ( Table 1). Gadd45 proteins are involved in cell-cycle regulation and are normally induced by genome damage and stress conditions, and regulate somite formation in zebrafish.…”
Section: Global Transcriptional Responses To Proteome Instability Indmentioning
confidence: 99%
“…eliminates also εA from ds and ssDNA [117], and thus may be a backup enzyme for ANPG glycosylase. Recently, it was shown that hABH2 repairs εC, as well, and probably competes with ANPG in the access to the lesion, since ANPG inhibits in vitro repair of εC by ABH2 [118].…”
Section: Oxidative Dealkylation By Alkb Enzymesmentioning
confidence: 99%